2015
DOI: 10.1186/s40064-015-1201-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community profiles of the colon from steers differing in feed efficiency

Abstract: Ruminal microbial fermentation plays an essential role in host nutrition, and as a result, the rumen microbiota have been a major focus of research examining bovine feed efficiency. Microbial communities within other sections of the gastrointestinal tract may also be important with regard to feed efficiency, since it is critical to the health and nutrition of the host. The objective of this study was to characterize the microbial communities of the colon among steers differing in feed efficiency. Individual fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 53 publications
9
45
0
Order By: Relevance
“…In any case, in accordance with our results, the relative abundance of Prevotella spp. has been shown to be increased in the ruminal liquid of inefficient (high residual feed intake) bulls (McCann et al, 2014) and in the colon from steers showing low feed efficiency traits (Myer et al, 2015c). Regrettably, the reasons behind different efficiency traits in these studies were not ascertained.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In any case, in accordance with our results, the relative abundance of Prevotella spp. has been shown to be increased in the ruminal liquid of inefficient (high residual feed intake) bulls (McCann et al, 2014) and in the colon from steers showing low feed efficiency traits (Myer et al, 2015c). Regrettably, the reasons behind different efficiency traits in these studies were not ascertained.…”
Section: Discussionmentioning
confidence: 84%
“…However, even though several studies have described the composition of microbiota in the rumen, jejunum, colon and caecum contents of steers or lambs differing in feed efficiency (Myer et al, 2015a(Myer et al, , 2015b(Myer et al, , 2015c(Myer et al, and 2016Santos et al, 2018b), there are scarce studies focused on ileal epimural microbiota of ruminants (Mao et al, 2015). This is surprising, since ileum is involved not only in nutrient absorption but also in the development of immune response (ileal Peyer´s patches, iPP) during early life.…”
Section: Introductionmentioning
confidence: 99%
“…Among the other notable effects was an increase in the sequence abundance for the genus Oscillospira in Eϩ steers after 14 and 28 days of grazing. One previous study has associated colonic Oscillospira presence with lowered ADG in crossbred steers (65). Oscillospira is a genus commonly found in both human and bovine gut microbiota (66,67) and is known to degrade host glycans in multiple species (68), thereby altering glycoprotein homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to findings described in previous reports (11,12,18) and suggests a succession of microorganisms colonizing the GIT that coalesces toward an adult composition. In particular, we observed that the GIT of neonate calves contain several taxa (i.e., Bacteroides, Prevotella, and Ruminococcus) known to be involved in the degradation of fiber and starch (25)(26)(27) and that are commonly identified in adult ruminants (28)(29)(30)(31)(32). These taxa were present as early as 1 week of age, when calves had been exposed only to liquid feeds, including colostrum and milk.…”
Section: Discussionmentioning
confidence: 99%